2012
DOI: 10.1080/09500340.2012.723756
|View full text |Cite
|
Sign up to set email alerts
|

Analytical expression for wave scattering from exponential height correlated rough surfaces

Abstract: Wave scattering from rough surfaces in addition the inverse scattering is an interesting approach to obtain the surface topography properties in various fields. Analytical expression in wave scattering from some known rough surfaces, not only help us to understand the scattering phenomena, but also would prove adequate to be a criterion to measure the information for empirical rough surfaces. For a rough surface with an exponential height correlation function, we derive an analytical expression for the diffuse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
2
3
0
Order By: Relevance
“…2 shows the dependence of the total normalized scattered field intensity, I tot , on the scattering angle, θ 2 , for different values of Hurst exponent, H. By decreasing H, fractional dimension of the surface will increase which is equivalent to increasing the roughness of the surface in the Euclidian space. As a result, the amount of reflected intensity in specular direction will decrease and contribution of reflection in other directions which appear in this approach and corresponds to diffuse component from rough surface will increase, which is in good agreement with the results obtained by Kirchhoff theory for rough surfaces [27].…”
Section: Equivalence Of 3d Scattering and Reflection In The Frac-tion...supporting
confidence: 91%
See 1 more Smart Citation
“…2 shows the dependence of the total normalized scattered field intensity, I tot , on the scattering angle, θ 2 , for different values of Hurst exponent, H. By decreasing H, fractional dimension of the surface will increase which is equivalent to increasing the roughness of the surface in the Euclidian space. As a result, the amount of reflected intensity in specular direction will decrease and contribution of reflection in other directions which appear in this approach and corresponds to diffuse component from rough surface will increase, which is in good agreement with the results obtained by Kirchhoff theory for rough surfaces [27].…”
Section: Equivalence Of 3d Scattering and Reflection In The Frac-tion...supporting
confidence: 91%
“…3. The total intensity for angles far from zero (non-specular angles) shows the diffuse intensity and it decreases by decreasing the wavelength which is in good agreement with the results obtained in [27].…”
Section: Equivalence Of 3d Scattering and Reflection In The Frac-tion...supporting
confidence: 90%
“…Since the publication of this seminal work by Berry, numerous studies have been published on related aspects of the problem, some of which can be found in Refs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The overall majority of these studies are either purely numerical and/or the scattered intensity is not obtained in a closed form expression but rather more typically as an infinite series where the terms depend on the self-affine parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, to accomplish the argument about effects of self-affinity in SHA in light metals, and effects of Gaussian and non-Gaussian of distribution functions of surface roughness in SHC, we explore the influence of the height-height correlation function on the SHA with self-affine surface roughness. The surface roughness will be regarded as effective impurities 27,28 and the power spectrum of isotropic rough surface will be described by k-correlation model [29][30][31][32] . The self-affine fractal surface roughness is characterized in addition to height fluctuations δ, from flatness and ξ by a local fractal dimension…”
Section: Introductionmentioning
confidence: 99%